PERSPEKTIF HUKUM KANONIK TERHADAP KEBEBASAN MENIKAH, PERKAWINAN SEJENIS, DAN PENOLAKAN KETURUNAN - Yanto Sandy Tjang; Mayong Andreas Acin (STP St. Bonaventura Medan, 2025)
This study explores in-depth the concept of freedom to marry within the framework of the Catholic Church’s Canon Law by examining three contemporary issues: the legal–moral capacity of prospective spouses, the Church’s position on same-sex marriage, and the juridical–moral status of couples who intentionally choose not to have children (childfree). Grounded in the Church’s teaching that marriage is a sacrament between one man and one woman—permanent, exclusive, and open to the gift of life—this research highlights that freedom and canonical capacity constitute fundamental prerequisites for the validity of the sacrament. Employing a qualitative approach through juridical-canonical analysis of the Code of Canon Law, magisterial documents, and contemporary moral theological scholarship, the study demonstrates that interior freedom and psychological maturity are essential elements in the giving of matrimonial consent. Furthermore, canonical impediments are understood as mechanisms safeguarding the integrity of the sacrament. Same-sex unions cannot be recognized either naturally or sacramentally, as they fail to fulfill the unitive and procreative dimensions of marriage. Likewise, an explicitly intended childfree choice may affect the validity of marriage as stipulated in Canon Law. The findings affirm the internal coherence of Canon Law in addressing modern moral challenges and present practical implications for marriage preparation, pastoral accompaniment, and moral formation. Consequently, this research contributes to a more comprehensive understanding of freedom to marry, the sacramental purpose of matrimony, and the juridical and pastoral issues emerging within contemporary social contexts.